Konseling Islam Melalui Terapi Sholawat Fatih untuk Mengatasi Career Anxiety pada Seorang Santri - Aprilia Halimatul Jannah; Ananda Syla Fatikha; Muhammad Azis Qoiri (STIKes Ibnu Sina Ajibarang, 2025)
This study aimed to evaluate the effectiveness of Islamic counseling using Sholawat Fatih therapy in addressing career anxiety in a student. A qualitative method with a phenomenological approach was employed, where the author served as a counselor providing guidance through Sholawat Fatih therapy. Data were gathered via in-depth interviews and analyzed descriptively to assess changes in the student's level of career anxiety. Descriptive analysis based on relevant literature data regarding the research variables was used for data interpretation. Instruments included observation sheets and comprehensive interviews. The Results of the study showed that individual counseling incorporating Sholawat Fatih therapy effectively reduced students' career anxiety levels..